Extraterrestrial hexamethylenetetramine in meteorites—a precursor of prebiotic chemistry in the inner solar system - Yasuhiro Oba (Nature Portfolio, 2020)
This manuscript tackles the origin of organic molecules in carbonaceous meteorites. Identifying hexamethylenetetramine in three carbonaceous meteorites, the authors propose formation from ammonia and formaldehyde by photochemical and thermal reactions in the interstellar medium, followed by the incorporation into planetary systems.